Generating social acceptability a case study on Sagittarius Mines Incorporated's innovative community and public relations approach - Magbanua, Jael A.
This single case study measured the effectiveness of the innovative community and public relations programs of Sagittarius Mines Incorporated in relation to generating social acceptability. The study also outlined the perceptions of the IP community including the rate of adoption and retention about SMI's different programs. A survey was conducted to know if the stakeholders viewed the presence of SMI as socially acceptable and if its strategies are working well for them. Furthermore, extensive interviews with SMI employees were also done to obtain necessary data. The study found out that innovative PR approaches and community relations strategy help in generating social acceptability. For the total adoption and retention of innovative programs, it should not only contribute to the betterment of the lives of its stakeholders, it should also be physically and culturally adoptable
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication